On the stability of the stabilized motion of a carrier rocket with a liquid-propellant jet engine and an onboard digital computer in the stabilization loop - Aleksandrov, Eugene; Aleksandrova, Tetiana; Kostianyk, Iryna; Morgun, Yaroslav (Національний технічний університет "Харківський політехнічний інститут", 2022)
The problem of choosing the values of the variable parameters of the digital stabilizer of the cosmic stage of a carrier rocket with a liquid-propellant jet engine and an onboard digital computer in the stabilization loop, which ensures stable movement of the stage along the entire active section of the flight trajectory, is considered. The effect of the stabilizer quantization period on the stability region of a closed-loop stabilization system is considered. It is recommended to choose the intersection of stability regions corresponding to uniformly distributed moments of time along the active section of the stage flight trajectory as acceptable values for the variable parameters of the stabilizer of a non-stationary stabilization object.

Розглядається задача вибору значень варійованих параметрів цифрового стабілізатора космічного ступеня ракети-носія з рідинним реактивним двигуном (РРД) і бортовою цифровою обчислювальною машиною в контурі стабілізації, що забезпечує стійкий рух ступеня уздовж усієї активної ділянки траєкторії польоту. Розглянуто вплив величини періоду квантування стабілізатора на область стійкості замкненої системи стабілізації. У якості області допустимих значень варійованих параметрів стабілізатора нестаціонарного об'єкта стабілізації рекомендується обирати перетин областей стійкості, що відповідають рівномірно розподіленим моментам часу уздовж активної ділянки траєкторії польоту ступеня.
Про стійкість руху, що стабілізується, ракети-носія з рідинним реактивним двигуном і бортовою цифровою обчислювальною машиною в контурі стабілізації
Keywords: cosmic stage of carrier rocket; digital stabilizer; variable stabilizer parameters; active section of flight trajectory; region of stability in the space of variable parameters; космічний ступінь ракети-носія; цифровий стабілізатор; варійовані параметри стабілізатора; активна ділянка траєкторії польоту; область стійкості в просторі варійованих параметрів